A chip-based scientific payload technology for visual detection of proteins and its application in spaceflight. (May 2020) - Li, Yongrui; Lv, Xuefei; Geng, Lina; Yang, Chunhua; Sun, Weiwei; Deng, Yulin
Abstract: Highly sensitive visual detection of proteins in space is often complicated, since bioassay payloads must achieve sensitive detection and environmental adaptability. Microfluidic chips enabling high degrees of integration and automation are a very promising approach for highly sensitive visualized protein detection in space. Here, we present a chip-based, highly integrated payload technology for the visual detection of proteins onboard the Tianzhou-1 cargo spacecraft. This device simply and tightly integrated multifunctional bioassay chips, complex fluid control, and execution of multiple programs to provide highly sensitive protein detection. Based on the delicate design of the microfluidic network, superparamagnetic immunoassay particles were successfully used to achieve immunoaffinity enrichment and visual detection in chips. This method demonstrated good performance compared to traditional visual test strips, showing limits of detection in the picomolar range for interleukin (IL)-6. Results measured in orbit indicated rapid visual detection of IL-6 in cell culture media, confirming the validity of the proposed approach for protein detection in space. Highlights: We developed a chip-based scientific payload technology for protein detection in spaceflight. Protein enrichment and detection were completed by superparamagnetic immunoassay particles in chips. Highly integrated device for protein detection onboard the Tianzhou-1 cargo spacecraft. Autonomic in-orbit enrichment and visual detection of IL-6 from cell culture media were achieved.